The 9th International Conference "Environmental Engineering 2014" 2014
DOI: 10.3846/enviro.2014.191
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of determination of real estate area

Abstract: Accuracy of determination of real estate area has a great importance nowadays, both in real estate selling and in tax assessment and also in spatial planning. Present and used in the past methods of area determination of parcels, buildings and dwellings cause thatthe quantity of areas are not consistent and at present this situation gives many questions. In the paper, discussion and analysis of methods of determination of areas of all types of estate in Poland, has been presented. Both methods used nowadays an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Therefore, it is very important that the information on the accuracy with which the position of the boundary points was determined was provided in a reliable manner. This is also important in the context of the mean errors of the analytical determination of the surface areas of the parcels (Bieda et al, 2014). It is worth noting that in accordance with Regulation (2011) the location of boundary points and boundary markers which belong to the fi rst-order fi eld details should be determined with a mean error of less than 0.10 m relative to the closest points of the horizontal geodetic control and the measurement control.…”
Section: Record Parcel and Its Boundariesmentioning
confidence: 99%
“…Therefore, it is very important that the information on the accuracy with which the position of the boundary points was determined was provided in a reliable manner. This is also important in the context of the mean errors of the analytical determination of the surface areas of the parcels (Bieda et al, 2014). It is worth noting that in accordance with Regulation (2011) the location of boundary points and boundary markers which belong to the fi rst-order fi eld details should be determined with a mean error of less than 0.10 m relative to the closest points of the horizontal geodetic control and the measurement control.…”
Section: Record Parcel and Its Boundariesmentioning
confidence: 99%
“…The upper limits of the values ranges corresponding to the previously mentioned att ribute formed the basis to estimate average errors of the surface areas in the article. This issue has already been a subject of broad analysis [1][2][3] on the basis of which, inter alia, it was demonstrated that the accuracy of the surface areas stated by the analytical method, apart from boundary points' location errors, infl uences also the number and placing of these points, which is basicly the geometry of a parcel.…”
Section: Evaluation Of the Scale And Scope Of The Infl Uence Of Averamentioning
confidence: 99%
“…It means that in this case, the infl uence of the accuracy of analytical evaluation of the surface area would be more signifi cant than the accuracy of a unit value estimation only if the errors of the boundary points location amounts to 3.00 m, which corresponds to the BPP equal to 5 and 6. However, it should be noted that the average error of the surface area depends also on the geometry of the parcel [1,2]. The analysis of the infl uence of surface area determination accuracy in the process of valuation of land properties and taking it into account would be well founded, also if the value of BPP att ributes equals 3 or 4.…”
Section: Evaluation Of the Scale And Scope Of The Infl Uence Of Averamentioning
confidence: 99%
See 2 more Smart Citations